Dragon Fruit (Hylocereus polyrhizus) Wine: Physical, Biochemical, and Organoleptic Preferences - Bunga, Senni Juniawati; Sir, Rikka Welhelmina; Hidayah, Zulianatul (Diponegoro University, 2025)
Dragon fruits (Hylocereus polyrhizus) are considered as one of the nutritious exotic fruits in Asian countries. Juice extracted from these fruits has been processed into wine by spontaneous fermentation. Fermentation was carried out for 21 days, and then wine aging was continued for 3 months. The biochemical properties (tartaric acid, alcoholic content, total soluble solids, reducing sugar content, color, and antioxidant activity) were determined using standard scientific procedures of food characteristics. The results after 3 months of wine aging show that a pH value of 3.51, a tartaric acid of 8.06%, an alcoholic content of 13%, a total soluble solid of 3o brix, a total reducing sugar content of 0.28 g/100 mL, a DPPH activity of 75.79%, and a chroma test score of 13.73. Sensory evaluation showed no differences in flavor, taste, aroma, and overall acceptability between the processed wine and a reference wine. The dragon fruit wine was generally accepted. Therefore, this study requires further comprehensive investigation into the substantial contents of functional compounds such as organic volatile groups and bioactive compounds.